Diretrizes para elaboração de medidas de prevenção contra quedas de altura em edificações - Martins, Miriam Silvério (2004)
Concepts, evolution and the importance of safety engineering are presented in this dissertation. The aspects that should be approached in the elaboration of the Conditions and Labor Environment Program for the Construction Industry are also considered, particularly the ones for activities that make falls from height possible. The difficulties of implementation of the program are analyzed, considering the characteristics of the Building Industry. Moreover, a case study carried out in the city of Londrina-PR is presented in order to find out the preventive measures against falls from height by building companies. Standards are presented for aid and parameters of safety design for collective protective equipment which approaches protection types, dimensions for calculations. Preventive measures against falls from height and forms of prevention are also presented. They consist basically in knowing the system and the construction process to be adopted by the company; evaluation of the risky and ergonomic situations in the activities of production in building plot; elaboration of collective preventive systems for the several production phases as well as the postoccupation phase; work training; specification of personal protective equipment for the production phases; documentation and evaluation of the safety system.